Analisis Lemak Babi Pada Produk Pangan Olahan Menggunakan Spektroskopi UV – Vis - Desi Ardilla; Muhammad Taufik; Dafni Mawar Tarigan; Muhammad Thamrin; Mariany Razali; Hendy Syahputra Siregar (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
The safety of processed food products is necessary to prevent food from possible of biological contaminants, chemical, and the others that may be harm of human health and conflict with religion, beliefs and culture of the community so that it is safe for consumption, including foods containing of pork so that it is necessary accurate method of analysis in the laboratory. This paper aims to analyze of pork in processed food products using UV-Vis Spectroscopy. Using spectrometric method, optimum wavelength was obtained at 270 nm, concentration was obtained in pig corned respectively 2,2703%, 35,3784%, 49,6351%, and 52,5405 %.